Functions h(t) and g(t) - Calculations

Choose a study mode

Play Quiz
Study Flashcards
Spaced Repetition
Chat to Lesson

Podcast

Play an AI-generated podcast conversation about this lesson
Download our mobile app to listen on the go
Get App

Questions and Answers

Simplify the expression: 1/(x - 1) + 1/(x^2 - 1)

(x + 2)/(x^2 - 1)

Simplify the expression: (x^2 - 1)/(x^2 - 2x + 1)

(x + 1)/(x - 1)

Simplify the expression: x/(x^2 - 1)

x/((x + 1)(x - 1))

Evaluate the limit as x approaches 1 of (x^2 - 1)/(x - 1)

<p>2</p> Signup and view all the answers

Flashcards

h(t) = t + 1/t

A function where 't' is added to its reciprocal.

h(-1)

The value of the function h(t) when t = -1.

h(2)

The value of the function h(t) for t = 2.

g(t) = t + 2 / (t - 2)

A function that involves addition and division. 't' is in the denominator.

Signup and view all the flashcards

g(0)

Value of the function g(t) when t = 0

Signup and view all the flashcards

g(a)

The function g(t) written in terms of 'a' instead of 't'.

Signup and view all the flashcards

Undefined g(t)

The function's output that is not defined due to division by zero.

Signup and view all the flashcards

g(2)

Value of the function g(t) for t = 2

Signup and view all the flashcards

function evaluation

The process of finding the value of a function for a given input value.

Signup and view all the flashcards

h(x-1)

The function h(t) with x-1 substituted in for t

Signup and view all the flashcards

Study Notes

Homework 24

  • Function h(t): A function is defined with a formula, h(t) = t/2 + 1/2 + 1/t.
  • Values of h(t):
    • h(-1) = -1/2 + 1/2 + (-1) = -1
    • h(2) = 2/2 + 1/2 + 1/2 = 2
    • h(1/2) = 1/4 + 1/2 + 2 = 9/4 = 2.25
    • h(x-1) = (x-1)/2 + 1/2 + 1/(x-1).
    • h(Ï€) = Ï€/2 + 1/2 + 1/Ï€

Function g(t):

  • Function g(t): Definition: g(t) = t+2 / t-2
  • Values of g(t):
    • g(-2) = -2+2 / -2-2 = 0/-4 = 0
    • g(2) = 2+2 / 2-2 = 4/0, Undefined
    • g(0) = 0+2 / 0-2 = 2/-2 = -1
    • g(a) = a+2 / a-2
    • g(a²-2) = (a²-2)+2 / (a²-2)-2 = a² / a²-4
    • g(a+1) = (a+1) + 2 / (a+1) - 2 = a+3 / a-1

Studying That Suits You

Use AI to generate personalized quizzes and flashcards to suit your learning preferences.

Quiz Team

More Like This

Function Evaluation and Graphs Quiz
5 questions
Function Evaluation and Representation Quiz
59 questions
Anthropometry and Bone Length Evaluation Quiz
5 questions
Mathematics Class 10 - Limits and Functions Quiz
5 questions
Use Quizgecko on...
Browser
Browser